Threshold effect of banking on income inequalities in developing countries: the importance of mobile money - Boniface Ngah Epo; Jules Médard Nana Djomo; Mark Wiykiynyuy Tangwa; Éric Dieudonné Obama Obama (African Governance and Development Institute (AGDI), 2023)
This study investigates the role that of mobile money on the effect of banking on income inequalities on a panel of 105 developing countries over a period from 1990-2019. We use the system GMMs estimator to examine this relationship for income inequality before as well as after taxes and transfers. Results show that increased in banking contributes to the upsurge in income inequalities in developing countries. Likewise, an increase in bank borrowing also contributes to an increase in income inequality in developing countries. These results were robust to spatial analysis for Sub-Saharan Africa and Latin America and the Caribbean. Policy enactment wise, developing countries should ameliorate mobile money services and access points to significantly reduce inequality.
Keywords: G20; O40; I10; I20; I32; 330; Mobile banking; developing countries; poverty; inequality